ПРИМЕНЕНИЕ ЗАПУТЫВАЮЩИХ ПРЕОБРАЗОВАНИЙ В КРИПТОГРАФИИ - Евгений Юрьевич Родионов (Безопасность информационных технологий, 2009)
The author considers various aspects of obfuscation technique towards white-box cryptography and its application for DRM solutions. This paper covers questions related with transforming symmetric encryption schemes into asymmetric and designing homomorphic encryption schemes.